2023
DOI: 10.1007/s42729-023-01514-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tolerance in Groundnut Plants Against Drought Stress and Cercospora Leaf Spot Disease with Exogenous Application of Arginine and Sodium Nitroprusside Under Field Conditions

Gehan Sh. Bakhoum,
Mervat Sh. Sadak,
Marian S. Thabet

Abstract: Naturally, under field conditions, plants are regularly experienced by a mixture of two or more stress factors. Drought is a major abiotic stress, and fungal pathogens characterize a main biotic stress challenge faced by plants and impact negatively on plant development and productivity. We propose that foliar application of nitric oxide (NO) donors can have positive effects on the induction of tolerance to biotic and abiotic stress on groundnut plants. This investigation was carried out to study the changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Disease resistance-signaling molecules such as jasmonate, salicylic acid (SA), and abscisic acid (ABA) are induced during pathogen infestation, with all these pathways playing crucial roles in regulating plant resistance to pathogens. 14,15 Studies have reported that β-aminobutyric acid enhances tobacco resistance to P. nicotianae by increasing SA content and decreasing ABA content. 16 Primary and secondary metabolites in plants, including amino acids, carbohydrates, lipids, and organic acids, undergo alterations to regulate cellular metabolism and maintain homeostasis under biological stress.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease resistance-signaling molecules such as jasmonate, salicylic acid (SA), and abscisic acid (ABA) are induced during pathogen infestation, with all these pathways playing crucial roles in regulating plant resistance to pathogens. 14,15 Studies have reported that β-aminobutyric acid enhances tobacco resistance to P. nicotianae by increasing SA content and decreasing ABA content. 16 Primary and secondary metabolites in plants, including amino acids, carbohydrates, lipids, and organic acids, undergo alterations to regulate cellular metabolism and maintain homeostasis under biological stress.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the context of plant–pathogen interactions, enzymatic activity and hormonal signaling are pivotal for plant resistance. Disease resistance-signaling molecules such as jasmonate, salicylic acid (SA), and abscisic acid (ABA) are induced during pathogen infestation, with all these pathways playing crucial roles in regulating plant resistance to pathogens. , Studies have reported that β-aminobutyric acid enhances tobacco resistance to P. nicotianae by increasing SA content and decreasing ABA content .…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength of photosynthetically active radiation (PAR) can be divided into long and short wavelength groups; a long wavelength, such as red color and near IR, is essentially used for photosynthesis in chlorophyll, and a short wavelength of PAR, such as blue and UV lights, involves ROS signal generation. , Thus, the quantity balance of long and short wavelengths of PAR could control the photosynthesis rate and the carbon metabolite flow as well as ROS levels in plants, and these might increase the biosynthesis of flavonoidal antioxidants such as saponarin and lutonarin. At the same time, the excess ROS generation could damage cell components and suppress the growth of plants and the accumulation of antioxidative metabolites. Recently, the effects of light quality and quantity on the growth and saponarin production in YBL were reported under light-emitting diode (LED) light; however, the accumulated saponarin concentrations and the biomass of YBL were lower than under sunlight conditions. , In the reports, the growth inhibition and phytotoxicity were shown over 400 μmol m –2 s –1 (PPFD) of a white LED light, even though it was significantly lower in light quantity than sunlight . To understand this, the light quality effect should be investigated on ROS generation, the photosynthesis rate, and the metabolites for saponarin.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the excess ROS generation could damage cell components and suppress the growth of plants and the accumulation of antioxidative metabolites. 33 36 Recently, the effects of light quality and quantity on the growth and saponarin production in YBL were reported under light-emitting diode (LED) light; however, the accumulated saponarin concentrations and the biomass of YBL were lower than under sunlight conditions. 17 , 23 25 In the reports, the growth inhibition and phytotoxicity were shown over 400 μmol m –2 s –1 (PPFD) of a white LED light, even though it was significantly lower in light quantity than sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, drought stress has become a major issue in agricultural production around the world. 69 As a more devastating stress factor, drought usually disrupts tissue water relations, nutrient absorption, and metabolic processes that makes the plants survival difficult to drought situations. 2 , 3 Drought also causes chlorosis and loss of cell turgidity, impairs net photosynthesis and root growth, assimilates translocation, imbalances membrane permeability, alters cell functions, and impairs enzyme activation and stomatal conductance, consequently reducing crop productivity.…”
Section: Introductionmentioning
confidence: 99%